Microestrutura e resistência a corrosão de ligas Cu-Al-Ni com adição de silício passíveis do efeito memória de forma - Aquino, Robson Cesar Alves de (2020)
In this work, the effects of silicon content on the microstructure and corrosion resistance of CuAlNi shape memory alloys were investigated. Additionally, the influence of the holding time of the solution treatment on the final as-quenched microstructure was also studied. Microstructural analyzes were performed using scanning electron microscopy, optical microscopy and x-ray diffraction techniques. Corrosion resistance evaluated in a NaCl solution medium using a cell containing 100 mL (pH = 7.0), both at a room temperature, through electrochemical and profilometry measurements. The results show that the addition of silicon did not promote considerable changes on the transformation temperatures of the CuAlNi alloys. On the other hand, the addition of silicon tends to reduce the grain size of the CuAlNi alloy and the corrosion resistance is substantially improved.